2020
DOI: 10.1001/jamanetworkopen.2020.23121
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Screening for COVID-19 in Asymptomatic Patients With Cancer

Abstract: As the coronavirus disease 2019 (COVID-19) pandemic continues across the United States, a critical issue for practicing oncologists is how to continue cancer care while protecting patients. 1 To continue care for patients while also minimizing exposure to health care staff, the Weill Cornell Medicine Division of Hematology and Medical Oncology created separate units for patients with confirmed COVID-19, patients with symptomatic but unconfirmed COVID-19, and asymptomatic patients with no known high-risk COVID-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
24
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 6 publications
(9 reference statements)
7
24
1
Order By: Relevance
“…The true burden of asymptomatic pediatric cases is still unknown, and several factors contribute to this problem, such as the age limits at certain testing centers and the discomfort associated with the swab. 23,24 The rate of positivity of 2.3% observed in our cohort was higher than the 0.6% through 0.9% described in oncological pediatric patients 9,11 and closer to the 2.2% reported in surgical pediatric patients. 10 In comparison, our estimates were higher than the pooled prevalence of 0.65% reported by Sola and colleagues.…”
Section: Discussionmentioning
confidence: 48%
See 3 more Smart Citations
“…The true burden of asymptomatic pediatric cases is still unknown, and several factors contribute to this problem, such as the age limits at certain testing centers and the discomfort associated with the swab. 23,24 The rate of positivity of 2.3% observed in our cohort was higher than the 0.6% through 0.9% described in oncological pediatric patients 9,11 and closer to the 2.2% reported in surgical pediatric patients. 10 In comparison, our estimates were higher than the pooled prevalence of 0.65% reported by Sola and colleagues.…”
Section: Discussionmentioning
confidence: 48%
“…The positivity rate described in our article is relatively low but within the range described in pediatric cohorts with medical conditions at large academic centers. [9][10][11]14 The incidence of COVID-19 that would justify the use of PCR screening in a dental practice has not been established. It has been proposed that mass testing with the goal of identifying asymptomatic carriers may be a necessary and effective strategy to limit the spread of the disease.…”
Section: Girls Boysmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noticed that although this result came from the region with a high number of cases, New York, PCR test positivity rate was very low among asymptomatic cancer patients. 6 In addition, Yin et al. showed that the asymptomatic infection rate in cancer patients from Wuhan was 2.9% (81 out of 2818).…”
mentioning
confidence: 99%